Unveiling Beauty Choices: How Lifestyle, Halal Label and Prices Form Emina Cosmetics Purchases - Dedldia, Desya; Hidayati, Rini (Research of Islamic Economics, 2025)
This study examines the influence of lifestyle, halal labeling, and price on purchasing decisions for halal cosmetics. The sample consisted of 100 respondents from the Faculty of Economics and Business at YARSI University, selected through purposive sampling. Data were collected using a questionnaire with the Judgement Sampling method and analyzed using multiple regression analysis, t-tests for partial effects, F-tests for simultaneous effects, and the coefficient of determination. The findings indicate that lifestyle has a positive and significant impact on purchasing decisions. Conversely, halal labeling and price do not have a significant effect. However, when examined collectively, lifestyle, halal labeling, and price significantly influence purchasing decisions. These results carry managerial implications for Emina Cosmetics, suggesting the need to develop marketing strategies that align with the lifestyles of young consumers, particularly female students. Companies should focus on tailoring products, promotional strategies, and brand communication to resonate with the lifestyle trends of this demographic. The originality of this study lies in its focus on the Islamic economic perspective of halal cosmetic purchasing behavior among young Muslim consumers, an area that has received limited attention in prior research.